From lignocellulosic biomass to furfural: insight into the active species of a silica-supported tungsten oxide catalyst - Bhaumik, Prasenjit; Dhepe, Paresh Laxmikant (ChemCatChem, 2017)
A sol–gel-synthesized silica-supported tungsten oxide catalyst that has Lewis acidity was characterized and employed as a solid acid catalyst in the synthesis of furfural directly from lignocellulosic biomass (isolated xylans and crop wastes). In a one-pot method, 71 % furfural formation from isolated xylan was possible using a water/toluene (1:2 v/v) biphasic solvent system at 170 °C after 10 h over 10 wt % WO3/SiO2. The WO3/SiO2 catalyst in the selective conversion of pentosan from crop wastes (bagasse, wheat straw, and rice husk) yielded 72–87 % furfural under the optimum reaction conditions. Additionally, the catalyst presented excellent recyclability in at least eight runs after simple water washing. From the catalyst characterization studies, it was suggested that silicotungstic-type acid species are anchored on the WO3/SiO2 catalyst that help to achieve a good catalytic activity.